Isolation, adaptation, and characterization of lumpy skin disease virus from cattle in Bangladesh - Pervin, Sumaiya; Ahamed, Md Mostakin; Chouhan, Chandra Shaker; Jahan, Md Salim; Ahmed, Rony; Nazir, K H M Nazmul Hussain; Siddique, Mahbubul Pratik; Rahman, Md Tanvir; Kafi, Md Abdul; Rahman, Md Bahanur (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The research aimed to isolate, adapt to cell culture, and characterize the lumpy skin disease virus (LSDV) from clinically infected cattle in Bangladesh. Materials and Methods: From September 2019 to June 2020, 37 skin nodules and skin swabs were aseptically collected from afflicted cattle in the outbreak regions of Jhenaidah and Kishoreganj in Bangladesh. The LSDV was isolated from embryonated specific pathogen-free (SPF) chicken eggs along the chorioallantoic membrane (CAM) route and the Vero cell line after several blind passages. The viral attachment protein was targeted for molecular detection using polymerase chain reactions (PCR). For phylogenetic analysis, PCR-positive products were partially sequenced. Results: The virus was evident in the cell line, showed cytopathic effects after the 13 blind passage, and on the CAM of SPF chicken eggs, exhibited thickening of the CAM with pock-like lesions. A total of 12 samples (32.43%) tested positive for LSDV by PCR. Phylogenetic analysis of the present isolates (accession numbers MN792649 and MN792650 ) revealed 100% similarity with strains from India (MN295064), Kenya (AF325528, MN072619, KX683219), Greece (KY829023), Serbia (KY702007), and Kazakhstan (MN642592); moreover, 99.43% to 100% similarity to the sheep pox virus. Conclusion: Partially sequenced LSDV was developed as a vaccine seed and was first isolated in Bangladesh and characterized at the molecular level. J. Adv. Vet. Anim. Res., 10(3):563–569, September 2023 http://doi.org/10.5455/javar.2023.j710